Strategi Perpustakaan Sekolah dalam Mendukung Pembelajaran STEM di Sekolah - Nurhayati (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Humaniora Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Todays schools are placing emphasis on STEM (an approach of learning that based on an idea of educate students in four specific subject: Science, Technology, Engineering and Mathematics). This approach of learning is important because continual advances of technology that affect the way student learn and interact, and the world economy is changing as well. It is said that current jobs may disappear and new job emerge as the impact of advance and automated system of technology. Through STEM students develop skills: problem solving, creativity, critical analysis, teamwork, independent thinking, initiative, communication and digital literacy. In line with above approach, a school library is as school’s physical and digital learning space where reading, inquiry, research, thinking, imagination, and creativity are central to students’ information-to-knowledge journey and to their personal, social, and cultural growth. Despite the emphasis on STEM, basic literacy skill through reading and writing are still important in curriculum. This article is based on the assumption rather than school choose between the priorities, literacy skill should be integrated with STEM through school library. School library can create maker activities in makerspace as resource-filled places of learning to enrich student experience in learning and develop students 21st century skills.